The Strategies and Problems Faced by Indonesian Teachers in Conducting e-learning during COVID-19 Outbreak - Rochyani Lestiyanawati (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2020)
COVID-19 outbreak had spread rapidly all over the world, impacting on the education system. The students had to study at home. Teachers were to apply online class in conducting the teaching and learning proccess. The school stakeholders also had to create a new management in supporting the school system. The objective of this research was to find out and describe the applied strategies and also problems faced by teachers in conducting e-learning during this COVID-19 outbreak. The findings showed that there were three teaching strategies applied by teachers; they were: applying only online chat, using video conference, and combining both online chat and video conference in online teaching and learning proccess. Some of problems also arose during the e-learning, totally 6 problems. The arisen teachig problems were: the teachers’ disability in accessing technology, school facilities in supporting e-learning, the difficulties in explaining the material, students’ limitation in accessing internet, students’ economically disadvantaged familiy background, and parents’ support system. Nevertheless, the teachers expressed that the e-learning system really relieve their responsibility in conducting teaching and learning proccess during this COVID-19 outbreak.